Perancangan Logo dan Standar Manual Grafis untuk Membangun Citra Identitas Badan Usaha Milik Desa Sukses Bersama Simpang - Dafy Cahya Nugroho; Alfian Candra Ayuswantana (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
A logo is a medium for communicating values, goals, and creating an impression of professionalism from an institution. Meanwhile, standard logo graphic manuals are a medium for communicating values, goals, and creating an impression of professionalism from an institution. These two elements are interrelated and inseparable. This journal discusses visual identity design, especially logos and graphic manual standards for the Sukses Bersama Simpang Village-Owned Enterprise which is implemented in the Merdeka College Competency Program (PKKM). Village Development Students at the East Java "Veteran" National Development University, Visual Communication Design Study Program were assigned to create a new logo design and standard graphic manual for the business entity. This design was carried out by means of direct observation, interviews and data collection through SWOT analysis. The aim of this design is to facilitate the identification of the Sukses Bersama Simpang Village-Owned Enterprise, reflect the institution's values and mission, and improve its image and reputation. Benefits include providing an impression of professionalism, increasing trust, and creating a strong, consistent identity. This program is carried out with the aim of community service carried out in Simpang Village, Prambon District, Sidoarjo Regency